APPLYING STRATEGY-BASED INSTRUCTION ON IMPROVING STUDENTS' READING COMPREHENSION ABILITY, STUDENTS' MOTIVATION, AND SELF-REGULATED LEARNING - Imam Sudarmaji; Yulia Ayu Lestari; bambang afriadi (Jurnal Evaluasi Pendidikan, 2022)
This present study is set out to examine and investigate the effect of using Strategy-Based Instruction as a new approach to teaching reading comprehension, students' motivation, and self-regulatory of students at SMK Lab Business School Tangerang. 30 students were used as a sample. To complete the aim of this study, a quasi-experimental approach is used as a one-group pretest-posttest and regression analysis. Students' motivation, self-regulated learning, and reading comprehension were assessed for all students in the treatment. Analyses examined treatment effects on reading comprehension, motivation, and self-regulated learning. Results from this strategy-based instruction treatment did not reveal statistically significant results for the effect of reading comprehension ability. There was no significant difference between observed and expected motivation and self-regulated learning frequencies on reading comprehension ability. However, there was a different value between the pretest and post-test of reading comprehension ability.